Expression of the Carbohydrate Lewis Antigen, Sialyl Lewis A, Sialyl Lewis X, Lewis X, and Lewis Y in the Placental Villi of Patients With Unexplained Miscarriages - Ma, Zhi; Yang, Huixia; Peng, Lin; Kuhn, Christina; Chelariu-Raicu, Anca; Mahner, Sven; Jeschke, Udo; von Schönfeldt, Viktoria (Frontiers in Immunology, 2021)
Lewis antigens including Sialyl Lewis A (sLeA), Sialyl Lewis X (sLeX), Lewis X (LeX), and Lewis Y (LeY) are a class of carbohydrate molecules that are known to medi¬ate adhesion between tumor cells and endothe¬lium by interacting with its selectin ligands, while their potential role in miscarriage remains enigmatic. This study aims to analyze the expression pattern of sLeA, sLeX, LeX, and LeY in the placental villi tissue of patients suffering unexplained miscarriage. Paraffin-embedded slides of placenta tissue from patients in early pregnancy (between 6 - 13 weeks, normal pregnancy (n = 18), recurrent (n = 15), and spontaneous (n = 20) miscarriage) were analyzed with immunohistochemical and immunofluorescent staining. Results of staining were evaluated with Immunoreactive Score (IRS). Expression of sLeA, sLeX, LeX, and LeY in the syncytiotrophoblast was significantly upregulated in the normal control group than spontaneous and recurrent miscarriage groups, but no prominent differences between the two miscarriage groups. Potential key modulators ST3GAL6 and NEU1 were found to be significantly downregulated in the recurrent miscarriage group and upregulated in the spontaneous group, respectively. Strikingly, LeX and LeY staining were also identified in the endothelial cells of villous vessels in the normal control group but not significant in miscarriage groups. To elucidate whether the villous vessels are prominently diminished in miscarriage placentae that might lead to the above observed different staining of LeX and LeY between groups, another cohort (n = 10 each group) of gestation ages-paired placenta tissue was selected to perform CD31 staining. Paired t-test found significantly diminished vessels in all size groups of villi (small villi < 200 µm, P = 0.0371; middle villi between 200 – 400 µm, P = 0.0010 and large villi > 400 µm, P = 0.0003). Immunofluorescent double staining also indicated the co-localization of LeX/Y and CD31. The expression of Lewis antigens and their modulators ST3GAL6 and NEU1 in the miscarriage placenta was significantly different from the normal pregnancy. For the first time, their expression pattern in the placenta was illustrated, which might shed light on a novel understanding of Lewis antigens’ role in the pathogenesis of miscarriages.